Heat stress effects on yield parameters of selected rice cultivars at reproductive growth stages - Aghamolki, Mohammad Taghi Karbalaei; Yusop, Mohd Khanif; Oad, Fateh Chand; Zakikhani, Hamed; Jaafar, Hawa; Syed Muhammad, Sharifah Kharidah; Musa, Mohamed Hanafi (WFL Publisher, 2014)
One of the overwhelming and deleterious effects of global warming on rice production is heat temperature resulting in rice crop during critical growth stages and consequently, yield and yield components decline. A glasshouse experiment has been conducted using randomised complete block design in split plot arrangement with four replications. The main plots included heat stress (38 ± 2°C), normal condition (32 ± 2°C) for day time and (22 ± 2°C) for night time. Sub plots included cultivars (Hovaze, Hashemi, Fajr and MR219) and sub-sub plot included different growth stages (booting, flowering and ripening). Yield and yield components (effective tillers, fertile spikelets, sterile spikelets, 1000 grain weight and aborted spikelets) were measured. All measurements were carried out utilising Standard Evaluation System for rice (SES, 2002) during the end of maturity stage. The main effects of heat stress and growth stage were significant on all parameters except on effective tillers. Furthermore, cultivar effect was found significant in all traits. Also, interaction effect of heat stress × growth stage × cultivar was significant on all parameters except for effective tillers. Heat stress decreased grain yield at flowering and booting, subsequently no significant difference was achieved at ripening stage in comparison with normal growth condition. Grain yield of all cultivars declined during heat stress comparing with normal condition, significantly. The lowest grain yield per pot was observed in Hashemi (6.8 g pot-1) at flowering stage during heat stress condition and the highest was found in MR219 (42 – 45 g pot-1) during normal condition. The greater fertile spikelets were found in MR219 receiving normal condition throughout the growing season. However, lesser number of fertile spikelets appeared by imposing heat stress during flowering and booting stages, respectively. The percentage of sterile spikelets was significantly higher in the heat stress treatment during flowering and booting stages. The maximum number of aborted spikelets was found in MR219 (14.5) at booting stage during heat stress condition. Thousand grain weight was reduced at booting and flowering stages during heat stress. In conclusion, the major reason for yield reduction of all cultivars was enhancement of sterile and aborted spikelet numbers when plants exposed to heat stress during booting and flowering phases. However, yield and yield components were not influenced by heat stress during ripening stage.